Cervical Cancer Detection from Cervix Image Using Pap smear Imaging through CNN - Bhuiyan, Mazedul Haque; Tabassum, Fariba; Bushra, Umme; Shwon, Md.Mahbub Rahman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.